Técnicas de manejo agropecuário sustentável - Paulus, Dalva (Org.) (2016)
The competitiveness in the rural sector and the need to make viable and sustainable property, direct the farmer to seek new production strategies. In this sense, the book Techniques of sustainable agricultural management has as objective contributed information on concepts, management practices, technological innovations, which are applicable in the agricultural production. The same is composed of 13 chapters, topics covered in aquaculture production, management and dairy production, as general aspects of hematology fish; dynamics of decision-making and adaptive flow dairy production systems; importance of performance measures and body biometrics in small ruminants; milk production in beef cows; parasitism in beef cattle; performance of dairy cows in production; efficiency of cross beef cattle in finishing phase; development of Marchangus: five years; and, bovine growth efficiency. In vegetable production area are addressed matters relating on management and olive cultivation, species of great economic importance and diversification as alternative on the property; functional foods in fruit and vegetables; influence of environmental factors, harvesting and drying in the production and composition of essential oils of Mentha spp; and, implication of the contamination of corn grain by mycotoxins in livestock production. At the end of the book, the expectation of the authors is to have contributed with relevant themes of Brazilian agriculture, which could reflect positively on knowledge, values and quality of available material.